Motives and expectations of students from Ukraine with respect to higher education in Poland in the field of tourism - Kapera, Izabela (Turyzm/Tourism, 2017)
The purpose of the research is to analyze the motivation and expectations of students from Ukraine with respect to higher education (HE) in the field of tourism. A survey questionnaire was created to be used by a target group in order to obtain their views. Research has shown that the main motive (60%) for studying in Poland was the desire to study and work at the same time. In reality HE students combined degree study and work in even more cases, and 58% of the work involved the tourism industry. Almost half of the students surveyed intend to remain in Poland following graduation. Those who expressed a desire to leave for other countries most often identified Spain and Germany. At the same time, most stated that they would like to work in professions associated with tourism including work in travel agencies and hotels.